2008
DOI: 10.1007/s11427-008-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myosin heavy chain composition of muscles on meat quality in Laiwu pigs and Duroc

Abstract: In order to explain the mechanism of high meat quality in Laiwu pigs and investigate the relation between myosin heavy chains (MyHC) composition and meat quality, meat quality analysis was conducted and mRNA expression of MyHC I, IIa, IIx, IIb was quantified by real-time fluorescence PCR in longissimus muscle (LM) and semimembranous muscle of Laiwu pigs and Duroc. The result indicated that, compared with Duroc, mRNA expression of MyHC IIa, IIx in LM and semimembranous muscle of Laiwu pigs was significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 19 publications
10
41
0
Order By: Relevance
“…In general, oxidative metabolism decreases in the rank order MyHCI → MyHCIIa → MyHCIIx → MyHCIIb (Lefaucheur et al, 2002), and these metabolic changes are consistent with the transition of MyHC profile toward a faster type (Lefaucheur et al, 2004). It is well-known that intensive selection for faster muscle growth in Western modern pigs has resulted in a shift in muscle fiber toward a higher glycolytic and lower oxidative metabolism (Lefaucheur et al, 2004;Hu et al, 2008;Guo et al, 2011), which is associated with leaner pigs, better feed efficiency and higher growth rate, but gives rise to a deterioration in meat quality (Lefaucheur et al, 2002;Shan et al, 2009). Previous studies have reported that, compared with the Landrace (Guo et al, 2011), Duroc (Hu et al, 2008) and Large White (Lefaucheur et al, 2004), respectively, the mRNA expression levels of MyHCIIa and MyHCIIx were greater in Jinhua, Laiwu and Meishan pigs, whereas the mRNA expression levels of MyHCIIb were lower.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…In general, oxidative metabolism decreases in the rank order MyHCI → MyHCIIa → MyHCIIx → MyHCIIb (Lefaucheur et al, 2002), and these metabolic changes are consistent with the transition of MyHC profile toward a faster type (Lefaucheur et al, 2004). It is well-known that intensive selection for faster muscle growth in Western modern pigs has resulted in a shift in muscle fiber toward a higher glycolytic and lower oxidative metabolism (Lefaucheur et al, 2004;Hu et al, 2008;Guo et al, 2011), which is associated with leaner pigs, better feed efficiency and higher growth rate, but gives rise to a deterioration in meat quality (Lefaucheur et al, 2002;Shan et al, 2009). Previous studies have reported that, compared with the Landrace (Guo et al, 2011), Duroc (Hu et al, 2008) and Large White (Lefaucheur et al, 2004), respectively, the mRNA expression levels of MyHCIIa and MyHCIIx were greater in Jinhua, Laiwu and Meishan pigs, whereas the mRNA expression levels of MyHCIIb were lower.…”
Section: Discussionsupporting
confidence: 59%
“…It is well-known that pork meat quality traits are affected by the genotype of the pig. For example, the Jinhua pigs (Miao et al, 2009;Guo et al, 2011) and Laiwu pigs (Hu et al, 2008) exhibited better meat quality traits when compared with the Landrace and Duroc pigs, respectively. Moreover, Ruusunen et al (2012) and Shen et al (2014) also found differences in meat quality traits between different genotype pigs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations